2011
DOI: 10.1007/978-0-85729-748-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Local Binary Patterns for Still Images

Abstract: The local binary pattern operator is an image operator which transforms an image into an array or image of integer labels describing small-scale appearance of the image. These labels or their statistics, most commonly the histogram, are then used for further image analysis. The most widely used versions of the operator are designed for monochrome still images but it has been extended also for color (multi channel) images as well as videos and volumetric data. This chapter covers the different versions of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(56 citation statements)
references
References 77 publications
0
53
0
Order By: Relevance
“…In experiments with facial images [32], it was found that 90.6 % of the patterns in the (8, 1) neighborhood and 85.2 % of the patterns in the (8, 2) neighborhood are uniform. Using uniform patterns instead of all the possible patterns has produced better recognition results in many applications [35]. By varying sampling radius R, LBP of different resolutions can be obtained, and thus, multiresolution analysis can be accomplished by combining the information provided by multiple operators varying (P, R) [36].…”
Section: Resultsmentioning
confidence: 99%
“…In experiments with facial images [32], it was found that 90.6 % of the patterns in the (8, 1) neighborhood and 85.2 % of the patterns in the (8, 2) neighborhood are uniform. Using uniform patterns instead of all the possible patterns has produced better recognition results in many applications [35]. By varying sampling radius R, LBP of different resolutions can be obtained, and thus, multiresolution analysis can be accomplished by combining the information provided by multiple operators varying (P, R) [36].…”
Section: Resultsmentioning
confidence: 99%
“…They are used in image processing for edge detection [5], texture representation [4] and texture discrimination [6]. Subsequently, they are found to be useful to process images prior to the LBP's feature extraction [12]. A Gabor filter basic formula is represented by , where is the Gabor filter carrier (complex sinusoidal), is the Gabor filter envelope (2D Gaussian-shaped function):…”
Section: The Gabor Filtermentioning
confidence: 99%
“…It thresholds the neighbourhood of each pixel and regards the result as a binary number. Because of its computational simplicity and discriminative power LBP texture operator has become a popular [14].…”
Section: Lbphfacesmentioning
confidence: 99%